Kreativitas Masyarakat Jorong Sampu dalam Upaya Pelestarian Tari Indang Tagak Nagari Lubuk Gadang Utara Kecamatan Sangir Kabupaten Solok Selatan - Yuniarti Dwi Putri; Hardi Hardi; Adriana Gusti (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to determine the Creativity of the Jorong Sampu Community in Efforts to Preserve Indang Tagak Dance Nagari Lubuk Gadang Utara, Sangir District, South Solok Regency, West Sumatra Province. The research method used is a qualitative research method which is descriptive analysis, namely describing and describing which is then analysed. This research uses creativity theory by Munandar and Edy Setyawati, preservation theory by Edy Sedyawati, supported by form theory by Y. Sumandiyo Hadi, and choreography theory by Rochana. The result obtained is that Indang Tagak dance is a traditional dance from Jorong Sampu which is still preserved by the community with its creativity. One form of creative effort is to develop the choreographic form of Indang Tagak dance by the Minang Saiyo Sakato studio which is hosted by the Takasiboe Community and arts institutions in South Solok Regency.